HOXB5 expression in oral squamous cell carcinoma - Renata Tucci; Marcia Sampaio Campos; Luciana Fasanella Matizonkas-Antonio; Marcelo Durazzo; Décio dos Santos Pinto Junior; Fabio Daumas Nunes (University of São Paulo, 2011)
Human HOX genes encode transcription factors that act as master regulators of embryonic development. They are important in several processes such as cellular morphogenesis and differentiation. The HOXB5 gene in particular has been reported in some types of neoplasm, but not in oral cancer. OBJECTIVE: The present study investigated the expression of HOXB5 in oral squamous cell carcinoma (SCC) and in non-tumoral adjacent tissues, focusing on verifying its possible role as a broad tumor-associated gene and its association with histopathological and clinical (TNM) characteristics. MATERIAL AND METHODS: RT-PCR was performed to amplify HOXB5 mRNA in 15 OSCCs and adjacent non-tumoral epithelium. A possible association with TNM and histopathologic data was verifed by the chi-square and post-hoc t-test. RESULTS: HOXB5 was amplifed in 60% non-tumoral epithelium and in 93.3% carcinomas. No statistically signifcant differences were found regarding the HOXB5 mRNA expression and TNM or histological grade. CONCLUSION: HOXB5 is expressed in OSCCs and its role in cancer progression should be further investigated.